(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Glycosylation is an important modification involved during embryonic development. Lectins are specific carbohydrate-binding proteins; they can be employed as specific probes to localize defined monosaccharide and oligosaccharides on cell surface and on cytoplasmic structures, and in extracellular matrix. Objectives:The lectins (SBA, PNA, WGA, SWGA, UEA-I) binding were used as a sensitive, stable, and easy tool that can provide an extraordinarily sensitive detection for changes glycosylation and carbohydrate expression that may occur during embryogenesis and development of trachea-esophageal region. Methods:Fertilized chick eggs were incubated at 38 °C, embryos were fixed with Bouin’s solution. Sections were treated with fluoresce ineisothiocyanate (FITC) labeledlectins. Results:The histochemical study during the 2ndand 3rddays of development revealed variable tempo-spatial variability of lectin bindings to the mesenchymal tissues and other embryonic structures at the trachea-esophageal region. Conclusions:The lectin bindings could be an indicator for the glycoconjucate changes that play an essential role in developmental phenomenon of trachea-esophageal morphogenesis by marking cellular differentiation, cellular migration, and cellular interactions. Key words:Trachea, esophagus, chick, embryo, lectin, histochemistry.